2017
DOI: 10.1016/j.toxrep.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diglycolic acid exposure to human proximal tubule cells in vitro and rat kidneys in vivo

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The relative mildness of 3-MCPD is also supported by our finding that KIM-1 levels neither appreciably rose in response to 3-MCPD treatment concentration nor to exposure duration. Although KIM-1 is an FDA-qualified biomarker of renal injury in vivo (Bonventre et al, 2010), it has also been demonstrated by multiple research groups to be a valuable in vitro cellular biomarker of proximal tubule cell injury (Luo et al, 2016;Mossoba et al, 2017;Veach and Wilson, 2018). KIM-1 expression is triggered in proximal tubule cells in response to a wide variety of toxic insults and has been shown to be part of a mitogenactivated protein kinase (MAPK)-mediated cell regenerative mechanism to repair injured cells (Song et al, 2019;Zhang and Cai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The relative mildness of 3-MCPD is also supported by our finding that KIM-1 levels neither appreciably rose in response to 3-MCPD treatment concentration nor to exposure duration. Although KIM-1 is an FDA-qualified biomarker of renal injury in vivo (Bonventre et al, 2010), it has also been demonstrated by multiple research groups to be a valuable in vitro cellular biomarker of proximal tubule cell injury (Luo et al, 2016;Mossoba et al, 2017;Veach and Wilson, 2018). KIM-1 expression is triggered in proximal tubule cells in response to a wide variety of toxic insults and has been shown to be part of a mitogenactivated protein kinase (MAPK)-mediated cell regenerative mechanism to repair injured cells (Song et al, 2019;Zhang and Cai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it bears the drawback of inefficiency and high cost. Although animal models exhibit high specificity for nephrotoxicity in drug dosage or safety pharmacology investigations, low sensitivity is also present [ 5 ]. In addition, due to species differences, many lead compounds with better potential were rejected as a result of their nephrotoxicity in animals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%